Comprehending Drug Use : Ethnographic Research at the Social Margins. - Page, J. Bryan (Studies in medical anthropology., 2010)
Comprehending Drug Use, the first full-length critical overview of the use of ethnographic methods in drug research, synthesizes more than one hundred years of study on the human encounter with psychotropic drugs. J. Bryan Page and Merrill Singer create a comprehensive examination of the whole field of drug ethnography-methodology that involves access to the hidden world of drug users, the social spaces they frequent, and the larger structural forces that help construct their worlds. They explore the important intersections of drug ethnography with globalization, criminalization, publ.